The Inertial Fractal Sets for Nonlinear Schrodinger Equations (Journal of Partial Differential Equations, 1995)
The existence of inertial fractal sets for weakly dissipative Schrödinger equations which possess (E_0, E) type compact attractor is proved. The estimates of the upper bounds of fractal dimension of inertial fractal set arc also obtained.